Clinical and Laboratory Evaluation of the Condition of the Oral Cavity in Children with Acute Leukemia - Lehenchuk, О. В.; Plyska , О. М. (Actual Dentistry, 2025)
Relevance: Leukemias are among the most common blood diseases in childhood. The state of the phagocytic system, the ability of phagocytic cells to absorb and digest microorganisms, significantly affects the development of various pathological diseases. Objective: To study the features of the clinical course of acute leukemias and the features of phagocytosis in the oral cavity, using the indicators of the phagocytic index, phagocytic number, and oxygen-dependent phagocytosis (NBT-test) to establish the leading clinical symptoms and features of the phagocytic activity of phagocytic cells of the oral fluid. Materials and methods. To achieve the set goals, 35 children aged 6 to 16 years with various forms of leukemia were examined. The subjects were divided into 2 groups: Group I — 19 children with acute lymphoblastic leukemia (ALL), of which 9 were in the first acute period, 4 in clinical remission, and 6 in relapse of the underlying disease; Group II — 16 children with acute myeloblastic leukemia (AML), of which 7 children were in the first acute period, 4 in clinical remission, and 5 children in relapse. Control group — 15 practically healthy children. Microscopic studies were performed, and the phagocytic activity of phagocytic cells of the oral fluid was studied. Results: Fungal lesions of the oral mucosa were diagnosed in 67% of children at the stage of treatment of the first acute period. The value of the phagocytic index during this period was 85.7 ± 5.8%, PN — 21.1 ± 0.7, NBT test index — 40.4 ± 1.86. In the control group: PF — 70.0 ± 5.1%, PF — 3.9 ± 0.6, NST test index — 17.6 ± 1.23. PI in this period was 85.7 ± 5.8%, PN — 21.1 ± 0.7, NST test index — 40.4 ± 1.86. In the control group: PI — 70.0 ± 5.1 %, PN — 3.9 ± 0.6, NBT test index —17.6 ± 1.23. At the stage of remission of ALL, gingivitis and candidiasis were the main clinical manifestations. The FI index was almost within normal limits — 73.8 ± 6, PN — 11.3 ± 0.6, NBT test — 23.7 ± 1.56. During relapse of ALL, 83% of children were diagnosed with “chemotherapeutic stomatitis” and fungal lesions of the mucosa. The phagocytic activity index was 88.3 ± 4.8%, PN — 25.3, and NST index — 46.4. At the stage of treatment of the first acute period of children with AML, fungal lesions of the oral mucosa were diagnosed in 71%, as well as hemorrhagic manifestations and acute herpetic stomatitis (28%). FI was 87.2%, FN — 16.1 ± 0.5, NBT — 41.6 ± 1.34. At the stage of remission of AML, gingivitis and fungal lesions of the oral mucosa were diagnosed in children. FI was 72.6 ± 5.9%. FN — 10.1 ± 0.4, NBT — 27.9 ± 1.86. During the period of relapse of AML, ulcerative-necrotic lesions of the mucous membrane, candidiasis, and hemorrhagic syndrome were detected in the oral cavity of children. FI was 89.1 ± 5.1, FN — 18.5 ± 0.2, NBT — 48.5 ± 1.05. Conclusion. Fungal lesions of the oral mucosa are the most characteristic clinical manifestation in the oral cavity in acute leukemias. Ulcerative-necrotic oral mucosa lesions are more often clinical manifestations of blood diseases in AML. The phagocytic activity of neutrophils in the oral fluid is increased at the stage of treatment of the first acute period and the stage of relapse. The protective forces of the oral fluid in acute leukemias have a high activity level. However, the ability to destroy microbial cells is significantly lower than that of phagocytic capture.